Response of bone marrow stromal cells to adipogenic antagonists. - Gimble, J M (1989)
Adipocytes constitute a major part of the bone marrow stroma in vivo and may play an active role in lymphohematopoiesis. Earlier studies had shown that the bone marrow stromal cell clone BMS2 was capable of adipocyte differentiation in vitro, in addition to its well-defined ability to support B lymphopoiesis. We now demonstrate that the process of adipogenesis in this functional bone marrow stromal cell clone can be inhibited by the cytokines interleukin-1 alpha, tumor necrosis factor, and transforming growth factor beta. Exposure of preadipocyte BMS2 cells to these agents blocked the induction of adipocyte differentiation as assessed by morphologic criteria and analysis of the neutral lipid content. Both interleukin-1 alpha and tumor necrosis factor elicited a rapid transient elevation in the steady-state mRNA levels of c-fos, c-jun, and JE. When added to differentiated adipocytes, the three cytokines continued to act as adipogenic antagonists. This was indicated by concentration- and time-dependent decreases in the activity of an adipocyte-specific enzyme, lipoprotein lipase. These changes in enzyme activity correlated directly with a decrease in steady-state levels of lipoprotein lipase mRNA. Another RNA marker of adipocyte differentiation (adipsin) was less influenced by the adipogenic antagonists. This may reflect the longer half-life of this mRNA transcript compared with those of lipoprotein lipase. Our results dramatically demonstrate that the differentiation state of bone marrow stromal cells can be modulated by exogenous factors in vitro. It is also the first report that transformation growth factor beta regulates the activity of lipoprotein lipase. These data suggest potential physiologic actions for these cytokines in vivo within the overall context of lymphohematopoiesis.